Manufacturing process-based storage degradation modelling and reliability assessment. (September 2018) - Ye, X.; Lin, Y.; Wang, Q.; Niu, H.; Zhai, G.
Abstract: Quality variations in manufacturing are significant factors for product's reliability. In this paper, a manufacturing process-based storage degradation modelling and reliability assessment approach is proposed to describe the uncertainty of product's storage degradation path caused by manufacturing process. Firstly, a storage degradation model of the output characteristic is constructed, by combining the functional relationship between output characteristic and bottom level performance (BLP for short, such as dimension, mechanical properties, material properties, etc.) with the storage degradation mechanism of products. This model is able to reflect the unit-to-unit variability of batch products. Secondly, based on finite element simulation and approximate modelling method, the unit-to-unit variability caused by manufacturing process is analysed, and the distribution characteristics of the random effect parameters (REPs) of the model are calculated accordingly. Finally, the storage reliability of the batch products is estimated based on the model and the calculated distribution characteristics of REPs. A case study of the aerospace relay is carried out to illustrate the effectiveness of the proposed approach.